Competence of university teachers: theoretical alternative (Papeles, 2011)
This article takes up literature on the subject of university teaching as well as research results, which argue the problem of the shortcomings of university teaching. As a solution to the problem, the concept of competence was proposed as an alternative to structure a possible model of university teaching. Thus, the article discusses the concept generally Competition, from several components: cognitive, metacognitive, social, contextual, factual and identity, from which is derived the concept Competence of university teachers. Thus: a) the context of university teaching is the university: education of subjects, professional training and curriculum building, b) the knowledge involved in cognitive and metacognitive processes are those concerning to the pedagogical-didactic located in professional scenarios, c) the construction of knowledge and learning is done in community, d) action has as aims transformation of the educational and professional fields, and e) it involves self-recognition, the recognition of others in the community and recognition of contexts.
Keywords: Competence; teaching; university